A network DEA aeronautical and non-aeronautical production model: An application to South Korea airports - Myung Je Lee; Changhee Kim (Journal of Economic Structures, 2018)
This study evaluates the overall efficiency of aeronautical and non-aeronautical production process. Moreover, it investigates the each stage efficiency using network data envelopment analysis and compares the results with tradition DEA to find out the causes of inefficiency and analyze its stage in detail. The framework for assessing the airports' performance was devised to capture the trend of airport industry and provide the multiple perspectives to decision makers. It results in the fruition that the aeronautical efficiency does not always guarantee the non-aeronautical efficiency. High air traffic was highly related to the aeronautical efficiency but non-aeronautical side of business could be the driving factors for the whole efficiency. Moreover, looking at sub-processes efficiency, the source of inefficiency could be found. Considering the combined and sub-process efficiency, it can be inferred that inefficiency in certain sub-process could be detrimental for the whole process or could be offset by other efficiency.
Keywords: 330; Aeronautical; Non-aeronautical; Network DEA; Efficiency analysis; South Korean airports